The effect of screen time on the circulatory system in children and adolescents (a review of studies in the regions of the world) - Emelianchik, Elena Yu.; Lapteva, Lyudmila V.; Kuular, Snezhana B.-T. (The New Research of Tuva, 2024)
The article provides an overview of scientific research on the impact of screen time on children's cardiovascular health. It considers the results of studies published between 2018 and March 1st, 2024, which assess the effects of screen time on functional state, metabolism, and cardiovascular health in children from different regions around the world.The analysis takes into account geographical location when considering research findings. Negative effects of screen use on cardiovascular health include eating disorders, sleep deprivation, decreased physical activity, elevated blood pressure, and increased levels of atherogenic lipids in children's blood. In Mongoloid children, there is a correlation between problematic screen use and obesity, especially among boys.